Air pollution and adverse cardiac remodeling: clinical effects and basic mechanisms - Liu, Yonggang; Goodson, Jamie M.; Zhang, Bo; Chin, Michael T. (Frontiers in Physiology, 2015)
EExposure to air pollution has long been known to trigger cardiovascular events, primarily through activation of local and systemic inflammatory pathways that affect the vasculature. Detrimental effects of air pollution exposure on heart failure and cardiac remodeling have also been described in human populations. Recent studies in both human subjects and animal models have provided insights into the basic physiological, cellular and molecular mechanisms that play a role in adverse cardiac remodeling. This review will give a brief overview of the relationship between air pollution and cardiovascular disease, describe the clinical effects of air pollution exposure on cardiac remodeling, describe the basic mechanisms that affect remodeling as described in human and animal systems and will discuss future areas of investigation.